Oral commentaries using movies in the ESL classroom / Noor Hanim Rahmat ... [et al.] - Rahmat, Noor Hanim; Ismail, Normah; Mohd Yunos, Rohayu (2014)
Oral commentaries in the ESL classroom has be taught in many ways. Traditionally, students are asked to prepare interesting titles for their oral presentation, and many may find it difficult to decide on their presentation titles. Brown (2001) listed several principles that teachers can consider when designing speaking techniques in the ESL classroom among which are to make sure that the content used are fun, meaningful and authentic to the students. The use of movies in oral commentary in the ESL classroom can be advantageous to the students in many ways. Movies help learners to focus on the content as well as meaning, thus making the students intrinsically motivated. Besides being a good example of authentic material, movies motivate students towards learning. In addition to that, activities used to incorporate the use of movies allow constructivist learning to take place. This quantitative study reports the survey done on students who have undergone a semester of using movies in the ESL classroom to make oral commentaries in the course ELC 230-Intergrated language Skills: Writing. Results of the study will have interesting implications towards the use of movies for students’ oral presentation